Stopped in its tracks: Negative regulation of the dynein motor by the yeast protein She1. (13th May 2013) - Moore, Jeffrey K.
Abstract : How do cells direct the microtubule motor protein dynein to move cellular components to the right place at the right time? Recent studies in budding yeast shed light on a new mechanism for directing dynein, involving the protein She1. She1 restricts where and when dynein moves the nucleus and mitotic spindle. Experiments with purified proteins show that She1 binds to microtubules and inhibits dynein by stalling the motor on its track. Here I describe what we have learned so far about She1, based on a combination of genetic, cell biology, and biophysical approaches. These findings set the stage for further interrogation of the She1 mechanism, and raise the question of whether similar mechanisms exist in other species. Abstract : Dynein motors power transport in a variety of cellular contexts. Transport is controlled by regulators that influence dynein motility and cargo‐binding. Recent studies from budding yeast identify a novel dynein regulator, She1, which regulates dynein by blocking the recruitment of dynactin and inhibiting dynein motility along microtubules.